Technology Entrepreneurship Project (ENT 600) : Nike / Mohamad Firdaus Mohamed Lazim - Mohamed Lazim, Mohamad Firdaus (2021)
When it comes to football, the first things that I think are about the sport is the shoes that comfortable, easy to wear and high quality with low price. Technology in the football shoes also need to be update in order to satisfy the customer’s need. I think Nike is the company that responsible to produce this shoe to satisfy the customers. Nike was founded in 1964 as Blue Ribbon Sports by Bill Bowerman, a track-and-field coach at the University of Oregon, and his former student Phil Knight. They opened their first retail outlet in 1966 and launched the Nike brand shoe in 1972. The company was renamed Nike, Inc., in 1978 and went public two years later. By the early 21st century, Nike had retail outlets and distributors in more than 170 countries, and its logo—a curved check mark called the “swoosh”—was recognized throughout the world. I believe Nike can make more high technology football shoes in the future. In order to satisfy customer’s need, Nike have to do research and review from customers. This research is based on my experience and other friends that play football.